2015
DOI: 10.1145/2845926.2845935
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic game theory and econometrics

Abstract: The traditional econometrics approach for inferring properties of strategic interactions that are not fully observable in the data, heavily relies on the assumption that the observed strategic behavior has settled at an equilibrium. This assumption is not robust in complex economic environments such as online markets where players are typically unaware of all the parameters of the game in which they are participating, but rather only learn their utility after taking an action. Behavioral models from online lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…We refer to Table 2 for the number of datapoints collected for the classes of users taking either public or private transportation. [Bajari et al, 2013;Syrgkanis, 2015]. These works employ a data-driven approach to analyzing the economic behavior of real world systems and agent interactions.…”
Section: Estimating the Stress Of Catastrophementioning
confidence: 99%
See 2 more Smart Citations
“…We refer to Table 2 for the number of datapoints collected for the classes of users taking either public or private transportation. [Bajari et al, 2013;Syrgkanis, 2015]. These works employ a data-driven approach to analyzing the economic behavior of real world systems and agent interactions.…”
Section: Estimating the Stress Of Catastrophementioning
confidence: 99%
“…Algorithmic Game Theory and Econometrics. Recently there has been a surge of interest in combining techniques from algorithmic game theory with the traditional goals of econometrics [Bajari et al, 2013;Syrgkanis, 2015]. These works employ a data-driven approach to analyzing the economic behavior of real world systems and agent interactions.…”
Section: Connections To Other Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithmic Game Theory and Econometrics. Recently there has been a surge of interest in combining techniques from algorithmic game theory with the traditional goals of econometrics [Syrgkanis, 2015]. In [Nekipelov et al, 2015] the authors developed theoretical tools for inferring agent valuations from observed data in the generalized second price auction without relying on the Nash equilibrium assumption, using behavioral models from online learning theory such as regret-minimization.…”
Section: Connections To Other Workmentioning
confidence: 99%